Managing the @humas_jabar Instagram Account as a Media for Innovation Diffusion - Rakha Andikha Teresna Sopandi; Iis Zilfah Adnan; Muhamad Erfan (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The rapid development of information and communication technology has significantly transformed public relations practices within government institutions. Social media has emerged as a strategic instrument for disseminating public information, emphasizing transparency, interactivity, and community participation. This study aims to analyze the role of the Public Relations Office of the West Java Provincial Government in managing the Instagram account @humas_jabar as an instrument for public dissemination. This research employs a qualitative approach with a case study design, using data collection techniques such as observation, in-depth interviews, and documentation. Data were analyzed using the interactive analysis model proposed by Miles, Huberman, and Saldaña (2019), while Rogers’ (2003) Diffusion of Innovations theory served as the conceptual framework to understand the communication strategies implemented by Humas Jabar. The findings reveal that the @humas_jabar account is managed systematically through stages of planning, production, and content distribution, emphasizing message relevance, visual strength, and participatory public engagement. The communication strategies adopted reflect the five key attributes of innovation diffusion: relative advantage, compatibility, complexity, trialability, and observability. Through a visual and interactive approach, Humas Jabar successfully establishes two-way communication between the government and the public, enhances public trust, and strengthens the image of the regional government as a transparent and responsive institution. Therefore, Instagram functions not only as an information medium but also as a strategic platform for realizing accountable and human-centered public communication governance in the digital era.